Estudo da arquitetura do sono, da sinalização de cálcio e apoptose na formação hipocampal de ratos adultos e senescentes submetidos à restrição crônica de sono - Souza, Luciane de [UNIFESP] (2010)
Aging leads to a progressive decrease in physiological capacity and increased vulnerability to respond to environmental stresses. Organic and functional alterations are frequently observed in advanced age. Memory impairment observed in this period is increased due to age-associated neurodegenerative diseases. Sleep disorders are also frequently observed in the elderly that have fragmented and less restorative sleep. The association of sleep loss and cognition impairment has been observed in human and animal model studies. Intracellular mechanisms have been studied to help elucidate age-associated alterations and the reason for high vulnerability related to stress conditions. The aim of this study was to evaluate the effect of age and chronic sleep restriction in the sleep parameters and cellular signaling, being composed by two parts: Part I - To evaluate the sleep pattern alterations in aged animals during a chronic sleep restriction protocol. Part II - To evaluate the effect of chronic sleep restriction in calcium signaling and cell death in the hippocampal formation of young and aged animals. The electrocortigram analysis showed that the aged animals had impairment in sleep recovery during the extended sleep restriction protocol. Aging also induced calcium signaling alterations in the hippocampal formation, since the aged animals had decreased response after glutamate stimulation and protonophore FCCP addition, that to release Ca2+ from mitochondria. The citosolic calcium increase was smaller than young animals. In the other side, the calcium release from thapsigargin-sensitive stores (as endoplasmic reticulum) did not suffer alteration in any of the groups. Chronic sleep restriction induced increase in the citosolic and mitochondrial calcium in the aged animals, without alterations in the endoplasmic reticular calcium. The increase in apoptotic nuclei was observed only in aged rats of both groups. However, there was more variability in the quantity of apoptotic nuclei in the sleep restricted group. Expression of Bcl-2 protein did not suffer alteration with aging in any of the groups. However, the expression in this protein was reduced in hypothalamus of aged rats. Our study indicated that aging promotes alterations in calcium homeostasis. Besides that, the aged-impairment observed in calcium signaling may be changed by chronic sleep restriction. These aged-alterations in calcium homeostasis may increase the cellular vulnerability and contribute to more stress and cell death. Our data indicate that calcium homeostasis imbalance induced by aging and sleep restriction may contribute to calcium signaling dysfunctions and/or cell death induction.